Os donos da terra: a disputa pelo destino da fronteira - aluta dos posseiros de Trombas e Formoso 1950/1960 - MAIA, Cláudio Lopes (2008)
In the decade of 1950 and in the first half of 1960, the middle north of Goiás was a place where occurred many fights for the land. This work seeks to discuss one of those movements which became known as the squatting fight of Trombas and Formoso. In this work it went through the various stages of that fight and it is analysed how in the process of the land dispute the squatting consolidated a group and created a common notion about the right to the land. In Trombas, the fight for the land made a group and conceived a solidarity which was mediated by the experience of the exploration lived by the peasants in the former period to their displacement for that small village of the north of Goiás. In that fight was also present the Brazilian Communist Party that by the very particular condition of its militants who were in Trombas was responsible for the consolidation of an alliance with the peasant ,structured in the claim for the land and in the consolidation of an autonomy of the movement. This work seeks to contribute with the debate on the border expansion and the capacity that the process had in Brazil to create spaces of dispute for the land by which groups and different interests were contended.